Gender Differences in Estimated Mortality Due to Hypertension Among Pregnant Women and Adults Aged ≥15 Years in Central Kalimantan Province, 2021 - Devi Savitri Effendy; Windi Wulandari; Wa Ode Siti Nurfauzah; Zahra Sa'ada Fatiyyah Tanzil; Wulan Sagitat Aprilianti; Wa Ode Aurela Utami Putri Djumain; Yuliana Safitri (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Hypertension is one of the most prevalent non-communicable diseases and remains a leading cause of morbidity and mortality worldwide. This condition substantially increases the risk of severe complications, including stroke and cardiovascular disease, and negatively affects patients’ quality of life. In Indonesia, including Central Kalimantan Province, hypertension represents a major public health concern, with a consistent increase in both incidence and mortality rates over recent years. According to the 2021 Central Kalimantan Provincial Health Profile, hypertension ranks among the top five causes of death, particularly affecting individuals of productive age and the elderly. Pregnant women and residents aged ≥15 years constitute high-risk populations that require targeted and comprehensive hypertension management strategies. Objective: This study aimed to analyze the estimated number of hypertension cases and hypertension-related deaths among individuals aged ≥15 years and pregnant women in Central Kalimantan Province in 2021, stratified by gender. Methods: A quantitative descriptive study design with narrative analysis was employed. Secondary data were obtained from the 2021 Health Profile of the Central Kalimantan Provincial Health Office. Results: A total of 646.208 individuals aged ≥15 years were identified as having hypertension, with the highest numbers reported in Kapuas Regency and Palangka Raya City. Overall, the prevalence of hypertension was higher among men, except in several districts, including East Kotawaringin and Lamandau, where female cases predominated. The highest number of hypertension-related maternal deaths was recorded in Kapuas Regency. Health promotion initiatives and the utilization of natural ingredients, such as red ginger and cucumber, demonstrate potential as complementary approaches to reducing hypertension-related risks. Conclusion: Comprehensive hypertension management is essential, particularly for vulnerable populations such as pregnant women and adults aged ≥15 years. Education-based interventions, supported by lifestyle modification and the use of natural remedies, may serve as effective strategies for hypertension prevention and control.